Analysis of Factors Affecting Underpricing Company Stock Prices at the Initial Public Offering (IPO) on the Indonesia Stock Exchange - Sisharini, Nanik; Kutu, Yestina Beatrix (Business Management Research, 2022)
This research purposes to determine an effect of ROA, ROE, DER, DAR, and CR to underpricing the company's stock price at Initial Public Offering on the IDX. The analysis uses multiple regression with the dependent variable underpricing stock prices at the time of the IPO, while the independent variables are ROA, ROE, DER, DAR and CR. The population in this study were companies that haved underpricing during the 2015-2019 period, while the sample used was 30 companies with the largest underpricing difference. The results showed that the variables ROA, ROE and CR had a significant effect on underpricing, while the variables DER and DAR had no effect on underpricing stock prices at the time of the IPO. This means that to invest more investors consider the return and company liquidity. Debt owned by the company is not a consideration for investors to invest.